2017
DOI: 10.1111/iju.13311
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and treatment of symptoms associated with indwelling ureteral stents: A systematic review

Abstract: Temporary drainage of the upper urinary tract by internal ureteral stents is a routine procedure in endourology. However, it is associated with a clear side-effect profile. Our aim was to evaluate prevention and treatment options of stent-related symptoms. We carried out a systematic review according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines using MEDLINE and SCOPUS, and identified 107 appropriate records. A high number of these studies showed clear methodological lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 60 publications
2
46
0
2
Order By: Relevance
“…A recent review published by Bestchart et al. has showed that LUTS were increased up to 60% after stent insertion [10]. In accordance with the literature, our study showed that ureteral stent insertion caused increasing scores on sections about LUTS of USSQ in groups 1 and 2 compared to the control group.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A recent review published by Bestchart et al. has showed that LUTS were increased up to 60% after stent insertion [10]. In accordance with the literature, our study showed that ureteral stent insertion caused increasing scores on sections about LUTS of USSQ in groups 1 and 2 compared to the control group.…”
Section: Discussionsupporting
confidence: 91%
“…The previous studies hypothesize that ureteric contractions and trigonal irritations due to ureteral stents and vesicorenal reflux through the ureteral stents lead to lower urinary tract symptoms (LUTS) [14]. A recent review published by Bestchart et al has showed that LUTS were increased up to 60% after stent insertion [10]. In accordance with the literature, our study showed that ureteral stent insertion caused increasing scores on sections about LUTS of USSQ in groups 1 and 2 compared to the control group.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Since that time, multiple design iterations, including introduction of the "Double J" configuration, which was designed to prevent migration into the kidney and bladder in 1978 (Finny 1978). Indwelling ureteral stents cause passive dilation of the ureter within the days to weeks after placement, facilitating stone passage and urine drainage (Berent 2011, Adin & Scansen 2011, Lennon 1997, Betschart 2017. In human urology, ureteral stents are most commonly used after ureterolith intervention, such as ureteroscopy and extracorporeal shockwave lithotripsy (SWL; Haleblian et al 2008).…”
Section: Ureteral Stentingmentioning
confidence: 99%
“…2,3 Betschart et al carried out a systematic review of 107 articles on ureteral stent-related symptoms. 4 The study suggested the effectiveness of alpha-1 blockers in reducing ureteral stent symptoms, and suggested that choosing an appropriate length of ureteral stent seemed beneficial for reducing symptoms. A network meta-analysis by Kwon et al showed that alpha-1 blockersespecially tamsulosin and alfuzosinreduced stent-related symptoms in seven randomized control studies.…”
mentioning
confidence: 99%